Production of pet food from fast food outlets wastes - Lau, Vincent Hui Chek (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Fast-food outlets such as KFC discarded all residual wastes generated from their daily sales. The waste consists of high amount of organic wastes which include chicken wastes, salad, rice and bun which finally end up in landfills. The chicken bones are tough and hence are rather slow in its natural degradation, which makes the mass disposal of chicken bones is potentially hannful to the environment. The aim of this research is to reuse the chicken wastes and process it into pet-food~ Simple steps such as washing and cleaning the chicken wastes including the meat, ligaments and cartilages were perfonned, followed by drying in an oven which removed the excess moisture and other organic matters. Once dried, the bones was crushed into smaller pieces, and then grounded into powder fonn on a dry blender. Mixture of the pulverised chicken waste with flour and other organic wastes such as egg shells and left over rice from KFC was mixed' into dough, using some oil and water, and may be fashioned into any desired shape. Once cooled, the fried dough can be used as pet food . Currently, only very small number of pet-food companies is based in Malaysia, and the use of discarded organic wastes from fast-food outlets may be seen as a possible alternative. The average amount of chicken wastes generated from a typical branch of KFC was about 8 kg per day. From this study, processing of 8 kg chicken waste, amended with other materials can produce at least 24 kg of pet-food, priced at RM51kg. As such, a monthly income of at least RM 3,600 from each branch is possible, just from the re-using and processing of the chicken wastes. In order to enhance the shelf-life, a minimum amount of preservative may be added.